Increasing Digital Literacy among Students at SDN Inpres Lik Layana Indah through Training Activities on the Use of Technology to Support Learning Activities - Andi Patmasari; Muhammad Ismail; Agussatriana; Abdul Kamaruddin; Dewi Satria Ahmar (Yayasan Ahmar Cendekia Indonesia, 2024)
The aim of this service activity is to increase digital literacy among students at SDN Inpres Lik Layana Indah through training activities on the use of technology to support learning activities. Service activity is carried out in several stages, namely first, the planning consists of forming a service team, determining partner, and analyzing partner needs and problems; second, the preparation in the form of coordination and initial socialization regarding the schedule; third, the implementation which consists of socialization, training and mentoring activities; and the final stage is reflection and evaluation. The service activity carried out by the service team consist of several activities, namely assistance in working on Class-Minimum Competency Assessment using smartphones, socialization on cyber security and attitudes as members of digital citizenship, training and assistance in using web browser, and graphic design training using the Canva application. All series of activities were carried out well and obtained satisfactory results as seen from the students’ enthusiasm when participating in the activities and the results of the pre-test and post-test analysis which showed an increase in students’ understanding after the service activity.